2010
DOI: 10.1016/j.conbuildmat.2009.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a bacterial carbonate coating on plaster samples subjected to the Calcite Bioconcept biomineralization technique

Abstract: Degradation of historical buildings is mainly due to the intrusion of water which is the main vector of pollutants. Different types of surface treatment have been proposed to avoid or limit this effect. One alternative to chemical treatments is the use of the carbonatogenesis property of some bacteria. This bacterial production has been evidenced on concrete and on limestone samples in an aqueous environment. However, the carbonate production was measured indirectly and the experimental protocol was far from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Previous studies have shown that strains have higher urease activity under neutral or alkaline conditions [34,35]. In this study, the strains were added to a medium containing urea and Cd 2+ at conditions of pH = 7 and 37 °C for Cd 2+ precipitation (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that strains have higher urease activity under neutral or alkaline conditions [34,35]. In this study, the strains were added to a medium containing urea and Cd 2+ at conditions of pH = 7 and 37 °C for Cd 2+ precipitation (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Recientemente se han publicado revisiones de lo más actual en cuanto a biocementación en concreto, sobre la precipitación bacteriana de carbonatos, los procesos químicos y su actividad de auto reparación de las bacterias incorporadas a los materiales para aplicación de calcita inducida microbiológicamente (Talaiekhozen et al, 2014;Verma et al, 2015) Experimentos sobre el tiempo de vida útil realizados sobre monumentos de roca caliza han mostrado un efecto protector de la capa de calcita depositada por la bacteria por varios años. Se ha sugerido que un nuevo tratamiento debería ser aplicado cada diez años (Castanier et El desgaste de los edificios es un problema generalizado que encontramos en muchas partes alrededor del mundo, ya sean hechos estos edificios de concreto así como edificios históricos hechos de rocas o ladrillos (Anne et al, 2010). En la ciudad de México existen una gran cantidad de monumentos considerados patrimonio histórico que presentan signos de daño, degradación y destrucción debido al incremento de la contaminación, factores medioambientales y biológicos.…”
Section: Introductionunclassified
“…Standard concrete experienced four times less water absorption than the mentioned mix, wherein the CS of the FA-included concrete was improved up to 22% [119]. In the initial stages of the crack formation, the mentioned autonomous healing technique could fill-in the crack, demonstrating its potential [120]. In brief, it was demonstrated that the autonomous healing approaches using vascular systems, capsules, and hydro gel encapsulation are effective in triggering the calcite precipitation in the concrete specimens and, thus, are capable of self-healing the concrete cracks.…”
Section: Bacteria-activated Self-healing Cementitious Materialsmentioning
confidence: 93%